Joints with angle dependent damping can help to reduce impact forces in robots - Shehara Perera; Saeed Bornassi; Mazdak Ghajari; Thrishantha Nanayakkara (Scientific Reports)
Abstract This paper investigates how a new angle-dependent damper design can help a robot to reduce collision forces. We designed a fluid-viscous angle-dependent damper by smoothly changing the clearance between the stationary and moving parts. Analytical and numerical simulation-based predictions were experimentally tested. Analytical modelling shows that angle-dependent damping has a $$48%$$ reduction in peak forces when compared to constant damping. Numerical simulations show that variable-gap dampers can change damping by $$134 ×$$ during a $$10 ×$$ gap change. The experimental findings confirm the analytical predictions by reducing collision force by up to $$10%$$ . These findings suggest that the angle-dependent variable damping solution could be used for robots that experience collisions such as industrial robotic manipulators, legged robots, perching robots, or robots that catch moving objects.